Hypertension literacy: Concept analysis - Kennedy Diema Konlan; Hyeonkyeong Lee; Eun Kyoung Choi (Wiley, 2023)
Abstract Aim Analysis of the concept of hypertension literacy to ensure clarity, reduce ambiguities and promote consistency in usage. Design Walker and Avant's concept analysis method was adopted. Methods Searched four electronic databases using keywords combined with the appropriate Boolean operators. After removing duplicates, thirty titles were identified, and ten articles met the basic criteria for inclusion. The analysis was done using a convergent synthesis design to integrate results and transform them into qualitative descriptions. Results Hypertension literacy's defining attributes were hypertension information search skills, comprehension of numeracy associated with blood pressure and medication and utilization of hypertension prevention information. The identified antecedents were formal education and improved cognitive, social, economic and health‐related experiences. Consequences of hypertension literacy included improved self‐reported and increased health awareness. Hypertension literacy allows nurses to assess and accurately improve knowledge and facilitate people to adopt prevention behaviours.